Dynamic changes in Japan’s prevalence of abnormal findings in cervical cytology depending on birth year - Ueda, Yutaka (Sci Rep, 2018)
Japan’s governmental recommendation of HPV vaccine has now been suspended for more than 4 years. In and before 2013, the targets of 20-year-old cervical cancer screening were females born in and before 1993, i.e., those who could not have received HPV vaccination because it was not yet publicly introduced. The targets during 2014–2019 are, or will be, those born in 1994–1999, i.e., those who came of age during a period with the highest HPV immunization rate. We analyzed the statistical data for each birth year, for the cumulative HPV vaccination rates achieved as of age 16, and for the corresponding results of cervical cancer screening at age 20. The rate of abnormal findings in cervical cytology increased slightly from 3.68% in 2010 (birth year: 1990) to 4.35% in 2013 (birth year: 1993); however, it dynamically dropped to 2.99% in 2014 (birth year: 1994) and 3.03% in 2015 (birth year: 1995). In total, the rate of abnormal findings in cervical cytology was 3.96% in 2010–2013, but significantly dropped to 3.01% in 2014–2015 (p = 0.014). This is the first description of dynamic changes occurring in the abnormal rate of cervical cancer screening as a result of positive changes in national HPV vaccination rates.